Maduranese Language Speech Level: A Sociolinguistic Study In Language Variety - Eko Heriyanto; Didit Kurniadi; Naela Hidayatul Mukaraomah (Journal of Language and Health, 2020)
This study investigates the analysis of speech level found in Maduranese language in accordance with the study of sociolinguistics. The speech level highly correlates with language variety which becomes one of the issues in sociolinguistics study. The researcher also tried to find out the influencing factors of Maduranese speech level and language variety in it. Hence, this research belongs to qualitative research which applied descriptive qualitative method. The method of collecting data was document/literature review through particular documents that have relation with the analysis of this research. To enhance the result of analysis, the researcher also conducted interview with the native speakers of Maduranese language. The finding of this research revealed that language variety occurs in the speech level of Maduranese language. Further, there are three speech levels in Madura which has similar type with the speech level in Java such as ngoko, krama madya and krama inggil. This kind of variations are caused by its use among different social classes or status among the society.